Molecular Receptors for Recognition and Sensing of Nucleotides. Issue 11 (11th December 2018) - Agafontsev, Aleksandr M.; Ravi, Anil; Shumilova, Tatiana A.; Oshchepkov, Aleksandr S.; Kataev, Evgeny A.
Abstract: Nucleotides are constituents of nucleic acids and they have a variety of functions in cellular metabolism. Synthetic receptors and sensors are required to reveal the role of nucleotides in living organisms and mechanisms of signal transduction events. In recent years, a large number of nucleotide‐selective synthetic receptors have been devised, which utilize different molecular designs and sensing mechanisms. This Minireview presents recent progress in the design of synthetic molecular receptors for selective recognition of nucleotides in aqueous solution. The binding properties of receptors and the origins of their selectivity for a particular nucleotide are discussed. Abstract : Molecular receptors and sensors for nucleotides are of considerable interest as they could help to reveal the role of nucleotides in living organisms and the mechanisms of signal transduction events. This Minireview presents the recent progress in the design of synthetic receptors for selective recognition of nucleotides in aqueous solution. The origins of the selectivity of receptors for a particular nucleotide are discussed.